Potential of Dioscorea Hispida dennst to Deflate Blood Glucose Level - Tukatman Tukatman; Heriviyatno Julika Siagian; Bangu Bangu (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Treatment of DM sufferers impacts the economic side related to the cost of drugs or pharmacological therapy, which is quite expensive. Gadung tubers (Dioscorea hispida dennst.) can be an option for people with diabetes because, in addition to containing low carbohydrates, they also contain several bioactive compounds that can be beneficial for the body. This study aims to analyze the effect of the consumption of Gadung tubers (Dioscorea hispida dennst) on the blood glucose levels of people with diabetes mellitus in Kolaka. This type of research is a quasi-experimental design using a one-group pre-post test design involving 30 men and women with DM who were recorded as active in Posbindu visits in Toari District taken purposively. The intervention was carried out for ten days for August – September 2021 by measuring the blood glucose levels of respondents before and after consuming processed Gadung tubers. The research data were analyzed using paired t-test. The results showed differences in the respondents' glucose levels before and after the intervention, where statistically, a p-value of 0.0001 less than 0.05 was obtained, which means that there was a significant effect of the consumption of Gadung tubers on the glucose levels of DM patients. This study concluded that processed yam could be an alternative food for people with diabetes.Perawatan penderita DM memberikan dampak pada sisi ekonomi dimana hal tersebut berkaitan dengan biaya obat atau terapi farmakologis tergolong mahal. Umbi gadung (Dioscorea Hispida) dapat menjadi pilihan bagi penderita DM karena selain mengandung karbohidrat rendah juga mengandung beberapa senyawa bioaktif yang dapat bermanfaat bagi tubuh. Studi ini bertujuan untuk menganalisis pengaruh konsumsi olahan ubi gadung (dioscorea hispida dennst) terhadap kadar glukosa darah penderita diabetes mellitus di Kolaka. Jenis penelitian ini adalah quasi eksperimental menggunakan desain one group pre post test design yang melibatkan 30 orang laki-laki dan perempuan penderita DM yang tercatat aktif dalam kunjungan Posbindu di Kecamatan Toari diambil secara purposive. Intervensi dilakukan selama sepuluh hari periode Agustus – September 2021 dengan pengukuran kadar glukosa darah responden sebelum dan setelah mengkonsumsi olahan umbi Gadung. Data penelitian dianalisis menggunakan uji t test berpasangan. Hasil penelitian menunjukkan bahwa terdapat perbedaan kadar glukosa responden sebelum dan setelah dilakukan intervensi, dimana secara statistic didapatkan p-value 0.0001 kurang dari 0.05 yang berarti ada pengaruh yang signifikan dari konsumsi umbi Gadung terhadap kadar glukosa penderita DM. penelitian ini menyimpulkan bahwa olahan ubi gadung dapat menjadi makanan alternative bagi penderita DM.